GAMBARAN KASUS HIV PADA IBU HAMIL DI DINAS KESEHATAN KOTA TEBING TINGGI PADA TAHUN 2017 - ELFA SUSANA (JURNAL ILMIAH KOHESI, 2019)
Hummanodificiency syndrome is not a problem that is underestimated again in fact it has threatened all levels of society of men and women until December 200 reported that 58 million people of the world were infected with HIV in that period 22 million died or 7,000 died from AIDS every day in Africa. HIV is still increasing in 2012 in Indonesia, there were 21,511 HIV cases and 5,686 AIDS cases. The aim of this study was to find out the description of HIV cases in the Tebing Tinggi City Health Office.This type of research is descriptive, the population in this study were all HIV sufferers in the Health Office of Tebing Tinggi City. In 2017 there were 19 people taking total sampling, the instruments used in the form of Distribution Tables and the data used were secondary data analysis data followed by discuss the results of research with existing theories and literature studies.From the results of this study it can be seen that the highest picture of HIV cases based on age is 2549 years old as many as 19 cases (100%), the highest occupation in commercial sex workers is 5 cases (26.3%), the highest risk factor is PLWHA with HIV partners 19 cases (100%).Based on the results of the study it can be concluded that of the 19 most age-based HIV cases found at the age of 25-49 years and based on the highest occupation of CSWs and based on the most risk factors for PLWHA with partners of HIV. It is expected that HIV health workers and supervision will detect HIV signs and symptoms in pregnant women